The role of organizational change to achieve strategic success A field research in the Petroleum Research & Development Center-Ministry of Oil - الطائي, علي حسون; ناجي, مصطفى ناطق (Journal of Economics and Administrative Sciences, 2015)
This current research deals with the "The role of organizational change in the achievement of strategic success" Who are getting increased attention to being one of the important topics and relatively new, And which have a significant impact on the future of the organization So there is a need for this research, which aims to identify the role of organizational change across dimensions (technology, organizational structure, human resources, organizational culture) in the strategic success through its components (a specific strategy, effective implementation, innovation, customer satisfaction)، And that by two main hypotheses, branched about eight hypotheses subset to study the relationship and impact between the variables, By a number of statistical methods, and used the questionnaire That have been subjected to a test of validity and reliability as a tool for measuring and collecting data from the research sample, which was distributed to 49 employees, and applied to the research community represented Managers and their assistants and heads of departments in the organization researched (R & D center of oil)   The research found a set of conclusions and recommendations including: The results showed that all the statistical correlations between the dimensions of organizational change and strategic success were strong and meaningful relationships as well as significance and influence were all meaningful significance, Which indicates the importance of the role of organizational change in the impact on achieving strategic success of organizations, And the study concludes with a set of recommendations was: increased attention to training through courses outside the center and developing a specialist training program to workers to encourage them to embrace the process of change، And the use of modern technology of electronic computing more effectively within the researched organization which contributes to the achievement of the strategic dimensions of success